The Impact of Three Dominant Factors on Employee Performance at PT. Arteria Daya Mulia: A Quantitative Approach - Kartono, Kartono; Dwi Vitaloka, Rheisya; Alwi, Muhammad (Ann Publisher, 2023)
The purpose of this study is to determine the influence of three main factors including leadership, compensation, and career development on employee performance at PT. Arteria Daya Mulia (ARIDA) Cirebon. All employees of PT. ARIDA became the population in this study. The sampling technique used is proportional stratified random sampling. This sampling technique is used if the population has heterogeneous and non-stratified elements. The sample taken in this study amounted to 87 respondents. The instrument used was in the form of a questionnaire while the data analysis carried out was multiple linear regression. According to the findings, leadership, salary, and career development, all have a favorable and significant impact on employee performance.